Da progressão do ensino elementar ao ensino secundário (1931-1945): crítica do exame de admissão ao ginásio - Minhoto, Maria Angélica Pedra (2007)
The object of this research is the admission examination for secondary education. In Brazil, it was established in 1931 and was used during 40 years to elect pupils to gymnasium. The analysis ranges between 1931 and 1945. The work aims at identifying: the social origin of pupils selected to secondary education, in Sao Paulo city; the variations on their performances at school; if such variations keep relation with social origin factors; if the exam results permit anticipate the students performance; the characteristics of the previous trajectory of the students that were successful in the exam; if the subjects covered by the exam produce any effect on primary education curriculum; the relation between the exam legal changes and the gymnasium social composition. The theoretical bases are: 1) David Hamilton s distinction between schooling and others institutionalized forms of education, and the different forms of schooling; 2) Norbert Elias effort to link the individual patterns of behavior and the structural changes of the society; and 3) Fritz Ringer s conceptual framework developed to study the European systems of secondary education, during the last three centuries. The empirical research collected data from the files of five educational institutions. The main results are: the social composition of secondary education in Sao Paulo was not restricted to the so called elite; the exam was inefficient to produce prognostics; the exam was not efficient to restrain the demand for secondary education; the social function of the exam was to legitimize a pattern of selection and to disguise the existence barriers in elementary education institutions; the selected social mobility of part of the students appeared as a sort of demonstration-effect , stimulating the demand for secondary education in Brazil; the legal regulation of the exam did not produce significant changes in the gymnasium social composition; the different strategies adopted by the private sector to circumvent the legal framework showed the limits of the Brazilian State both as a repressive agency and as a development inducer in the field of education